Optimizing 21st Century Learning Strategies in Improving Basic Competencies of Elementary School Students: A Literature Study - Samsidar Samsidar (PT. Anagata Sembagi Education, 2024)
The transformation of education in the 21st century demands learning that emphasizes not only content mastery but also the development of critical, collaborative, creative, and communicative thinking skills. Elementary schools, as the primary level of education, have a strategic role in instilling these skills from an early age. This study aims to systematically examine 21st-century learning strategies and their relevance to improving the achievement of Basic Competencies (BC) in elementary school students. The method used is a qualitative literature study by analyzing scientific sources from journals, books, and educational policy documents published in the last five years. The results of the study indicate that strategies such as Project-Based Learning, flipped classrooms, and the STEAM approach are highly effective in encouraging the achievement of BC holistically. However, challenges in implementation remain, such as limited teacher competency, lack of supporting infrastructure, and the lack of systemic integration of innovative approaches into the curriculum. Therefore, policy support, strengthening educator capacity, and the provision of a collaborative learning ecosystem are needed to optimize these strategies. This study has important implications for the development of basic learning that is adaptive and relevant to the needs of the times.